Um modelo econométrico com parâmetros variáveis para a carga tributária bruta brasileira trimestral - Mário Jorge Mendonça; Cláudio Hamilton dos Santos; Luis Alberto Medrano (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This article presents a linear econometric model with variable coefficients for the analysis of the quarterly dynamics of the Brazilian gross tax burden in the 1995-2008 years.The choice of this particular model was motivated by the constant changes made in the Brazilian tax system during these years - most frequently in the scope, design, and size of pre-existing taxes, but once in a while also the elimination of some of these taxes and/or the creation of new ones. The main conclusions of the paper are that: (i) GDP is, quite certainly, the main explanatory variable of the dynamics of the quarterly tax burden during the period in question; (ii) the share of the quarterly Brazilian tax burden that does not depend on GDP (or on any other variable, for that matter) increased quite significantly during the latter period - possibly due to continuous improvements on the ability of the Brazilian government to raise tax revenues and/or increases in the size of the economy's formal sector; and (iii) the GDP-elasticity of the Brazilian tax burden appears to have fluctuated around values well below unity, contrarily to what estimates based on models with constant coefficients would lead us to believe.
Keywords: H20; H22; C32; 330; Steuerbelastung; Brasilien; Brasilien